2018
DOI: 10.1002/rnc.4400
|View full text |Cite
|
Sign up to set email alerts
|

Mean square stability of linear stochastic neutral‐type time‐delay systems with multiple delays

Abstract: This paper studies mean square exponential stability of linear stochastic neutral-type time-delay systems with multiple point delays by using an augmented Lyapunov-Krasovskii functional (LKF) approach. To build a suitable augmented LKF, a method is proposed to find an augmented state vector whose elements are linearly independent. With the help of the linearly independent augmented state vector, the constructed LKF, and properties of the stochastic integral, sufficient delay-dependent stability conditions expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…This section will show that it is possible to design a u(y(t − 𝛼), 𝛾(t ), t )(0 < 𝛼 < 𝜏) that makes the controlled HNSNMJS (27) AS and ES in the sense of p-th moment and almost surely.…”
Section: Stabilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This section will show that it is possible to design a u(y(t − 𝛼), 𝛾(t ), t )(0 < 𝛼 < 𝜏) that makes the controlled HNSNMJS (27) AS and ES in the sense of p-th moment and almost surely.…”
Section: Stabilizationmentioning
confidence: 99%
“…Most of the existing results are for the case containing only one retarded derivative of the state. However, many practical systems have multiple time delays [26][27][28][29], which may bring about more complex instability, and undoubtedly makes the research much harder. Song et al [30] first explored the almost surely asymptotic stability of a class of HNSNMJSs with multiple delays, and they found that the stability of the system only depends on the delays of the drift term.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark In some engineering systems (eg, heat exchangers, distributed networks, and car‐like robots), time‐delay is encountered in both the states and their derivatives 31 . This promotes the scientific research on neutral time‐delay systems.…”
Section: Problem Formulation and Preliminariesmentioning
confidence: 99%
“…Shen et al studied the stability of the hybrid NSDDEs with highly nonlinear coefficients and they solved those systems with a single delay in Reference 20. However, lots of real systems have multiple time delay states (see, eg, References 23‐26). Therefore, we will further investigate the stability of the hybrid NSDEs with multiple delays, where their coefficients are highly nonlinear.…”
Section: Introductionmentioning
confidence: 99%